Effects of trace element levels on platelet aggregation - Kurtoglu, E; Ugur, A; Baltaci, AK; Halifeoglu, I (Springernature, 2004)
Platelet aggregation was measured by an optical method in 32 patients with iron-deficiency anemia at the time of diagnosis and after a period of Supplementation with iron. Epinephrine- and adenosine diphosphate-induced platelet aggregation were lower in anemic patients than in the controls (p<0.05). After iron-supplementation therapy, these values showed no significant differences. If induced by collagen or ristocetin, platelet aggregation was the same for patients and controls, but increased after treatment of patients (p<0.05). The plasma zinc values did not show significant differences among the subjects included in this study. These results show that iron is involved in the enzymatic systems that regulate platelet aggregation. The exact nature of this interaction is still to be determined.
Keywords: platelet aggregation; trace elements; iron-deficiency anemia; iron supplementation